ANALISA POTENSI LIKUIFAKSI BERDASARKAN NILAI N-SPT DI BANDARA INTERNASIONAL KUALANAMU MEDAN - Juniarso Juniarso; Andi Asnur Pranata M H; Ellysa Ellysa (Jurnal Ilmiah Desain & Konstruksi, 2024)
Liquefaction is a phenomenon where soil that was originally solid changes to liquid due to increased pore water pressure during earthquake vibrations. Liquefaction analysis is usually carried out using data from measurements and field analysis, as well as numerical simulations to predict the potential for liquefaction to occur at a location. In liquefaction analysis, there are several methods that can be used, such as the SPT (Standard Penetration Test) method, CPT (Cone Penetration Test). Kualanamu International Airport is an international airport that serves the Mebesarro area and is the central airport of North Sumatra Province. This airport is located in Deli Serdang Regency, 23 km east of Medan city center. In this research, an analysis of the potential for liquefaction in the soil at Kualanamu International Airport will be carried out to prevent damage to the structure above, loss of life and large economic losses. Calculation of liquefaction potential is carried out by comparing the ratio between the maximum cyclic stress and the effective stress on a soil or rock element exposed to cyclic loads (Cyclic Stress Ratio / CSR) with the ratio between the maximum resistive cyclic stress and the effective stress of the soil (Cyclic Resistance Ratio / CRR). The results of the analysis provide information that the potential for liquefaction occurs at a depth of > 1.5m to a depth of > 5m, where the soil above this depth is dominated by sandy soil with an SF value of ≤ 1.0 for each drill point.